2019
DOI: 10.1007/s11947-019-02283-1
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Pulsed Electric Field Treatment for the Extraction of Bioactive Compounds from Blackcurrant

Abstract: The objective of this work was to enhance the bioactive compounds extraction of blackcurrant using pulsed electric fields (PEF) technology. An experimental design was performed to find the best PEF conditions using the desirability approach and response surface methodology. The effect of the electric field strength and the treatment time over the total polyphenolic content (TPC) and the antioxidant activity (AA) was analyzed. The optimum treating conditions were found to be 1318 V/cm and 315 pulses, and result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(21 citation statements)
references
References 36 publications
(42 reference statements)
0
21
0
Order By: Relevance
“…Another factor that affects the yield of the extraction is the initial temperature of the process. Thus, Gagneten et al [ 97 ] evaluated the effect of the initial temperature at 10 or 22 °C. They observed that the efficiency of the extraction was higher at 22 °C.…”
Section: Extraction Methods Used To Extract Anthocyaninsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another factor that affects the yield of the extraction is the initial temperature of the process. Thus, Gagneten et al [ 97 ] evaluated the effect of the initial temperature at 10 or 22 °C. They observed that the efficiency of the extraction was higher at 22 °C.…”
Section: Extraction Methods Used To Extract Anthocyaninsmentioning
confidence: 99%
“…In addition, they observed that during the extraction the temperature increased 5 °C in both experiments and the correlation with the electric current was linear. Thus, cold temperatures can provoke a decrease in the electroporation efficiency [ 97 ]. This technique has been applied to improve the extraction efficiency of anthocyanins in different natural matrices.…”
Section: Extraction Methods Used To Extract Anthocyaninsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pulsed electric field (PEF) is an innovative non-thermal processing technology regarded as environmentally friendly due to its low energy expenditure water depletion [ 1 ]. PEF technology has been successfully used to extract anthocyanins from different matrices [ 94 , 95 , 96 , 97 , 98 ]. As shown in Table 2 , PEF technology improved anthocyanin extraction from different agri-food by-products compared to conventional extraction technologies or even other innovative extraction technologies (e.g., US and high voltage electrical discharges).…”
Section: Innovative Processes For Anthocyanin Extraction From Agri-food By-productsmentioning
confidence: 99%
“…Several emerging technologies have been employed to recover phytochemical compounds from biomasses inside a biorefinery approach or even aiming for bioactive compounds extraction from by-products or residues. Innovative techniques such as low-frequency ultrasound [ 64 , 65 ], supercritical CO 2 [ 34 , 66 ], pressurized liquids [ 47 , 67 ], high-pressure processing [ 68 , 69 ], pulsed electric fields [ 70 , 71 ], and others, allow the recovery of bioactive compounds using non-thermal treatments and green solvents. In this way, the extracts obtained by these techniques are promising in technological applications for enhancing food quality and health attributes since they are free of toxic solvents.…”
Section: Innovative Processes For the Extraction Of Phytochemical Compoundsmentioning
confidence: 99%